D-Tangent Surfaces of Timelike Biharmonic D-Helices according to Darboux Frame on Non-degenerate Timelike Surfaces in the Lorentzian Heisenberg Groupill - Korpinar, Talat; Turhan, Essin (Soc Paranaense Matematica, 2014)
In this paper, we study D-tangent surfaces of timelike biharmonic D-helices according to Darboux frame on non-degenerate timelike. surfaces in the Lorentzian Heisenberg group H. We obtain parametric equation D-tangent surfaces of timelike biharmonic D-helices in the Lorentzian Heisenberg group H. Moreover, we illustrate the figure of our main theorem.
Keywords: D-Biharmonic curve; D-tangent surfaces; Darboux frame; Heisenberg group